Utilization of muddy detritus as organic matter source by the fan mussel Pinna nobilis. - TRIGOS, S.; GARCÍA-MARCH, J.R.; VICENTE, N.; TENA, J.; TORRES, J. (Mediterranean Marine Science, 2014)
The knowledge of the feeding habits in marine species is fundamental to better understand their relationship with the environment. Although phytoplankton has been traditionally reported as the main food source consumed by the Mediterranean fan mussel Pinna nobilis, recent studies have revealed that detritus represents an important food source for this species. We analysed the degree of acceptance of muddy detritus and the utilisation of its organic matter (OM) by P. nobilis on a group of 21 individuals (30.3-59.7 cm of total shell height (Ht)). The specimens were collected between July and September 2012 in two areas (43°04´25” N; 5°46´7” E and 43°04´34” N; 5°47´32” E) of the Embiez archipelago, northwestern Mediterranean (France). Our studies show that P. nobilis retains high quantities of OM from muddy detritus (47.50 ± 11.23% of filtered OM) irrespectively of shell size. Smaller individuals, however, actively filter more detritus than large ones. The values of retained OM, together with previous studies on stomach contents, suggest that muddy detritus is a more important OM source than phytoplankton for this species.